2007
DOI: 10.2739/kurumemedj.54.25
|View full text |Cite
|
Sign up to set email alerts
|

GnRH Agonist Acts as Ovarian Protection in Chemotherapy Induced Gonadotoxicity: An Experiment Using a Rat Model

Abstract: Summary:To reduce chemotherapy induced gonadotoxicity, co-treatment with gonadotropin releasing hormone against analogue (GnRHa) was tested using rat model. Leuprorelin acetate (Leuplin) with or without cisplatin (CDDP) was given subcutaneously at a dose of 9.4 μg/ml to Wistar strain female rats. The total number of follicles was counted and the maturation of follicles was evaluated at the largest section of the ovary on the 5th and 10th day after administration. Leuplin led the ovary to a resting phase in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
(18 reference statements)
0
11
1
Order By: Relevance
“…A limited number of studies prove that paclitaxel and cisplatin damage primordial follicles, which constitute the major part of ovarian reserve (5, 6). Matsuo et al (7) reported that the gonadotoxic effect of cisplatin may be prevented by a GnRH agonist, the cytotoxic effects of paclitaxel with cisplatin, on primordial and mature follicles. The role of the GnRH agonists in the prevention of cytotoxic effect of paclitaxel, alone or combined with cisplatin has been evaluated in the present experimental study for the first time in the literature.…”
mentioning
confidence: 98%
“…A limited number of studies prove that paclitaxel and cisplatin damage primordial follicles, which constitute the major part of ovarian reserve (5, 6). Matsuo et al (7) reported that the gonadotoxic effect of cisplatin may be prevented by a GnRH agonist, the cytotoxic effects of paclitaxel with cisplatin, on primordial and mature follicles. The role of the GnRH agonists in the prevention of cytotoxic effect of paclitaxel, alone or combined with cisplatin has been evaluated in the present experimental study for the first time in the literature.…”
mentioning
confidence: 98%
“…As for the effects of CDDP on rat ovary, decreases in primordial follicles and Müllerian inhibiting substance, which is produced by the primordial and small ovarian follicles, were observed after a single dose of CDDP (Borovskaya et al, 2004;Yucebilgin et al, 2004;Yeh et al, 2006). Repeated dosing of CDDP during 1 or 2 estrous cycles in rats induces a decrease in the total number of follicles and large follicles are more sensitive to the toxic effects of CDDP than small follicles (Shinagawa, 1998;Matsuo et al, 2007). However, the mechanism of CDDP ovarian toxicity is not well known.…”
Section: Sp77mentioning
confidence: 99%
“…Our study has demonstrated that CDDP caused significant toxicity in the ovarian tissues of rats. Matsuo et al (2007) reported that GnRH agonists are useful against chemotheraphy induced ovarian toxicity. They claimed that addition of Leuprorelin acetate protected primordial follicles from harmful effect of CDDP.…”
Section: Discussionmentioning
confidence: 99%